2020
DOI: 10.21203/rs.3.rs-19940/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of alkaline water intake on gastritis and miRNA expression (miR-7, miR-155, miR-135b and miR-29c)

Abstract: Background : It is known that abnormal expression of miRNAs in the gastric cancer (GC) contributes to its carcinogenesis. Therefore, ingestion of commercial (usual) water on a daily basis may be a contributing factor for the occurrence of alterations in the gastric mucosal. In this study, it was evaluated the expression of the miRNAs miR-29c, miR-7, miR-155, and miR-135b in the gastric tissue of patients with gastritis before and after the consumption of alkaline water (pH range from 8.0 to 10.0), as well as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In 2020, a recent study made by Chavez et al highlighted the effects of crenotherapy with alkaline water (pH=8.0-10.0) administered for five months for gastritis symptom relief. The results showed that besides the beneficial effect of crenotherapy with alkaline water on gastritis symptoms, an improvement in the RNA expression was present, the alkaline water intake significantly increasing the expression of various genes related to the digestion process (34).…”
Section: Evidence-based Literature Data Focused On the Benefit Of Crenotherapy For Gi (Gastrointestinal) Tract Pathologiesmentioning
confidence: 99%
“…In 2020, a recent study made by Chavez et al highlighted the effects of crenotherapy with alkaline water (pH=8.0-10.0) administered for five months for gastritis symptom relief. The results showed that besides the beneficial effect of crenotherapy with alkaline water on gastritis symptoms, an improvement in the RNA expression was present, the alkaline water intake significantly increasing the expression of various genes related to the digestion process (34).…”
Section: Evidence-based Literature Data Focused On the Benefit Of Crenotherapy For Gi (Gastrointestinal) Tract Pathologiesmentioning
confidence: 99%